Spectrum of hypocalcaemia after thyroid surgery in Dhaka Medical College Hospital - Chowdhury, Anup Kumar; Fakir, Abu Yusuf; Islam, Md Nazmul; Abedin, Syed AM Asfarul; Arafat, Mohammad Shaharior; Saha, Bishwojit Kumar (Bangladesh Medical Journal, 2019)
Hypocalcaemia is not a uncommon complication after thyroid gland surgery. The extent of surgery and expertise are the vital factors to determine the spectrum of hypocalcaemia. This study was done to observe the spectrum of hypocalcaemia after different extent of thyroid gland surgery. A total of 70 consecutive patients were enrolled in the study by purposive sampling who received treatment for thyroid disorder in department of ENT and Head Neck Surgery, Dhaka Medical College Hospital, Dhaka, Bangladesh. They underwent different extent of thyroid surgery from January, 2017 to June, 2017. A prospective study was conducted for this 6 months period. A pre-structured, interview and observation based, peer reviewed data collection sheet was prepared. Data regarding sociodemographic, clinical, surgical and outcome profile were recorded. Data were compiled, edited and analyzed with SPSS version 23. Data were presented as mean and standard deviation, frequency percentage and median with range. The mean age of the respondents was 46.79±6.79 years (age range: 36-73 years.). Male to female ratio was 1:2.3. All the patients underwent total, near total, subtotal and completion thyroidectomy. 35(50%) and 28 (40%) patients underwent surgery due to papillary thyroid carcinoma and multinodular goiter respectively. Total of 30 patients developed hypocalcaemia. Among them, 22(73.33%) developed asymptomatic or mild hypocalcaemia which subsequently developed symptomatic hypocalcaemia (26.67%). Out of these 30 patients,15(50%) and 10 (33.33%) patients developed hypocalcaemia intraoperative (20 minutes after surgery) and after 24 hours after surgery respectively. Serum calcium level significantly decreases after total thyroidectomy and most critical time is the first 24 hours of post thyroidectomy period. Bangladesh Med J. 2018 Jan; 47 (1): 1-5